Clinical and microbiological studies of periodontal disease in Sjogren's syndrome patients - (:unkn) unknown (WILEY, 2002)
Background: Little is known about the periodontal status of patients with Sjogren's Syndrome (SS), a chronic inflammatory autoimmune disease characterized by xerophthalmia and xerostomia. The aim of the present study was to evaluate whether the periodontal status of SS patients, in terms of clinical and micro biological parameters, differs from systemically healthy age- and gender-matched controls. Methods: 8 primary SS and 10 secondary SS patients were examined in comparison with 11 control subjects. All patients were diagnosed by the European Community Criteria. Control subjects were systemically healthy and not undergoing periodontal treatment. The comparison of clinical status was made in terms of mean periodontal parameters (plaque index, gingival index, gingival recession, probing pocket depth, probing attachment level and bleeding on probing) as well as the frequency distribution of probing pocket depth and probing attachment level measurements. Microbiological assays of the subgingival dental plaque samples were carried out by both a chairside enzyme test (Periocheck(R)) for the detection of peptidase activity (PA) and a polymerase chain reaction (PCR) analysis for 9 selected periodontal micro-organisms (Actinobacillus actino-mycetemcomitans, Fusobacterium nucleation, Prevotella intermedia, Treponema denticola, Porphyromonas gingivalis, Eikenella corrodens, Campylobacter rectus, Bacteroides forsythus, Streptococcus oralis). Results: The occurrence, severity and extent of periodontal lesions were not significantly different between the 3 patient groups for all periodontal parameters examined. No significant differences in the sub-gingival plaque samples from control, primary or secondary SS patients for the PA test, frequency or type of periodontal micro-organisms observed. Conclusion: No significant differences could be detected in either clinical or microbiological parameters of primary or secondary SS patients compared with that of control subjects. The results of the present study thus support the notion that the periodontal status of patients with SS do not differ from systemically healthy age- and gender-matched controls.
Keywords: Sjogren's syndrome; periodontal status; microbiology; peptidase activity; polymerase chain reaction; SUBGINGIVAL PLAQUE SAMPLES; DL-ARGININE-NAPHTHYLAMIDE; GINGIVAL CREVICULAR FLUID; POLYMERASE CHAIN-REACTION; PORPHYROMONAS-GINGIVALIS; ACTINOBACILLUS-ACTINOMYCETEMCOMITANS; TREPONEMA-DENTICOLA; BACTEROIDES-FORSYTHUS; DNA-PROBES; PREVOTELLA-INTERMEDIA